Annotated legal documents on Islam in Europe / Volume 15 Sweden / compiled and annotated by Mosa Sayed, Göran Larsson - Sayed, Mosa (Annotated legal documents on Islam in Europe, 2017)
Status of religious communities -- Constitutional guarantees: a historical overview -- Legal registration of religious communities -- State support for Islamic religious communities -- Muslims in integration laws -- Mosques and prayer houses -- Burial and cemeteries -- Education and schools -- Compulsory education -- Religious education -- Independent schools -- Further and higher (tertiary) education -- Islamic religious education training at universities -- Islamic chaplaincy in public institutions -- Employment, social laws and discrimination -- Religious holidays -- Islamic slaughter and food regulations -- Islamic goods and services -- Islamic dress -- Criminal law -- Male circumcision -- Female genital mutilation -- Forced marriages -- Family law -- Private international law -- Marriage and divorces -- Spouses' matrimonial property rights -- Inheritance law -- Substantive family law -- Marriage -- Divorce -- Spouses' matrimonial property rights -- Inheritance law -- Children -- General considerations -- Islamic custody and fostering in Swedish law -- Bibliography